Impact of body mass index on short-term outcomes following gastric and colorectral cancer surgery - Yuksel, Cemil; Gojayev, Afig; Aydin, Ferit; Unal, Ali Ekrem; Demirci, Salim (Annals of Medical Research, 2022)
Aim: The present study aims to investigate the effect of high body mass index (BMI) on short-term outcomes and survival in patients following intra-abdominal malignancy surgery. Materials and Methods: The study was carried out in Ankara University, Department of Surgical Oncology. We retrospectively analyzed the data of patients who underwent gastrectomy and colectomy for malignancy in our clinic between August 2019 and August 2020. BMI was calculated by dividing body weight (kg) by height (m) squared. The patients were classified into two groups as normal (< 25.0 kg/m2 ) and overweight (≥ 25 kg/m2 ) in terms of BMI. Results: 158 patients were included in our study. 78 (49.3%) had undergone surgery for gastric cancer and 80 (50.7%) for colorectal cancer. 73 (46.2%) patients were female and 85 (53.8%) male. The mean age was 61.50±13.37. Fifty four (34.2%) patients had BMI < 25 kg/m 2 and 104 (65.8%) of them were ≥25 kg/m 2 . 57.6% of the patients operated on for gastric cancer and 75.6% for colorectal cancer had high BMI, and the difference between the two groups was statistically significant (p = 0.01). An investigation of relationship between BMI and mortality revealed that 37 with BMI ≥25kg/m2 and 5 with BMI < 25kg/m2 died. The difference was statistically significant (p < 0.001). Conclusion: BMI is an important factor affecting postoperative morbidity and mortality in patients with gastric and colorectal malignant tumors. In the present study, we show that overweight may be associated with severe postoperative complications and poor prognosis in these patients. We suggest that surgeons be highly aware of BMI to make effective treatment plans in gastric and colorectal cancer cases
Keywords: Body mass index; gastrointestinal tumors; laparoscopy; morbidity; prognosis